TRANSPORT OF BOTTOM WATERS THROUGH THE VEMA FRACTURE ZONE IN THE MID-ATLANTIC RIDGE - Demidov A.N.; Dobrolyubov S.A.; Morozov E.G.; Tarakanov R.Y. (My University, 2007)
This paper is dedicated to the study of structure and transport of deep and bottom waters through the Vema Fracture Zone (11° N) in the Mid-Atlantic Ridge. In 2006, during an expedition onboard R/V Akademik Ioffe, a survey of 25 CTD-stations was carried out in the study region with a size of 15 × 15 km over the main saddle of the Vema Fracture Zone at 41° W. Strong spatial variability of water mass characteristics was found in the study region. A strong easterly flow was found in the main part of the channel with velocities up to 30 cm/s. This flow includes Antarctic Bottom Water (AABW) and lower part of the North Atlantic Deep Waters (NADW). It was found that the transport of AABW is within 0.11–0.64 Sv (1 Sv = 106 m3/s). A decrease in the potential temperature of bottom waters by 0.027°C was found compared to 1994.